2015
DOI: 10.1080/07481187.2014.951495
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of Death Depression Scale Among Nurses

Abstract: This study is an attempt to investigate validity and reliability of the Persian version of Death Depression Scale among male and female nurses at Jundishapur University of Medical Science and 2 private hospitals in Ahvaz, Iran, who were selected by a convenience sampling method after obtaining informed consent. They completed the Death Depression Scale-Revised (DDS-R), Death Anxiety Scale, Death Obsession Scale, as well as Short-Form of Beck Depression Questionnaire (BDI-13). The results of exploratory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Many studies have shown a positive relationship between death anxiety, death depression, and death obsession on one hand, and general anxiety, obsession, and depression on the other (5,18,19). Naderi et al found that death anxiety is different among nurses in various hospital wards, whereas no significant difference was observed with respect to other variables, such as optimism and sense of humor (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown a positive relationship between death anxiety, death depression, and death obsession on one hand, and general anxiety, obsession, and depression on the other (5,18,19). Naderi et al found that death anxiety is different among nurses in various hospital wards, whereas no significant difference was observed with respect to other variables, such as optimism and sense of humor (36).…”
Section: Discussionmentioning
confidence: 99%
“…This scale was developed by Templer et al in 1990 to assess depression symptoms associated with death. DDS-R contains 15 items, rated on a five-point Likert-scale (No, 1; very much, 5); the scores ranged from 19 to 95 (19). Al-Sabwah, Abdel-Khalek, and Tomás-Sábado et al measured Cronbach's alpha and test-retest reliability coefficients for this scale in an interval of four weeks and reported values equal to 0.92, 0.90, and 0.87, respectively (20,25).…”
Section: Death Depression Scale-revised (Dds-r)mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores on the DDS indicate more death depression (Fischer & Corcoran, ). Several studies have demonstrated that the DDS has good internal consistency, validity and reliability (Abdel‐Khalek, , ; Aghazadeh, Mohammadzadeh, & Rezaie, ; Almostadi, ; Alvarado, Templer, Bresler, & Thomas‐Dobson, ; Dadfar, & Lester, ; Dadfar, & Lester, in press; Mohammadzadeh, Rezaei, & Aghazadeh, ; Rajabi et al, ; Sharif Nia et al, ; Templer et al, , ; Tomás‐Sábado & Gómez‐Benito, ; Tomás‐Sábado & Limonero, ; Tomas–Sabado et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Abdel‐Khalek and Lester () found that Egyptian (mainly Muslim students) had higher religiosity scores than did British (mainly Christian) students but lower subjective well‐being, while Abdel‐Khalek and Lester () found that Kuwaiti students had significantly higher fears of death than did American students. There has also been some research on death concerns among Iranian Muslim nurses (See Aghajani, Valiee, & Tol, ; Bagherian, Iranmanesh, Dargahi, & Abbaszadeh, ; Dadfar, Asgharnejad Farid, Atef Vahid, Lester, et al, ; Dadfar, & Lester, , , ; Dadfar, Lester, Atef Vahid, Asgharnejad Farid, & Birashk, ; Naderi, Bakhtiar Poor, & Shokouhi, ; Rajabi, Begdeli, & Naderi, ). The 8A model is based on the transTtheoretical model (TTM) introduced by Chan, Tin, Chan, and Chan () for the Empowerment Network of Adjustment to Bereavement and Loss in End‐of‐life (ENABLE) programs.…”
Section: Problem Identificationmentioning
confidence: 99%